OMNICHANNEL MARKETING STRATEGY AND ITS IMPACT ON CUSTOMER SATISFACTION IN RETAIL - Parmini Parmini; Farida Akbarina (Adisam Publisher, 2025)
The development of digital technology has changed consumer shopping behavior and prompted retail businesses to adopt omnichannel marketing strategies. This literature review aims to analyze the role of channel integration, service consistency, personalization of customer experience, and speed of response and after-sales service on customer satisfaction. The review results indicate that channel integration simplifies transactions and reduces purchasing barriers, while consistent service across all touchpoints strengthens customer trust. Data-driven personalization can create relevant shopping experiences and increase perceived value, while faster response times thru technologies like chatbots and real-time support contribute to customer loyalty. This finding confirms that a well-planned and technology-supported omnichannel strategy can enhance retail competitiveness in an increasingly competitive market. This study also recommends further research with an empirical approach to quantitatively measure the direct influence of these variables on customer satisfaction and loyalty.